Postsecondary Student Mobility from College to University: Academic Performance of Students - Gerhardt, Kris; Masakure, Oliver (Canadian Journal of Higher Education, 2016)
This paper considers the impact of transfer credits on the GPA of college–university transfer students. The data come from the academic records of students enrolled at 2 different campuses at an undergraduate university in Ontario across a 4-year period. The results from multivariate regression analyses show that the number of transfer credits is significantly associated with a higher GPA, controlling for student status (part time/full time), campus of study, cohort, semester of study, and previous college background. Further analysis suggests that the credit–GPA relationship is nonlinear, peaking at 6 transfer credits. These findings can be used to help inform individuals and institutions about the past performance of students as further refinements to transfer policies between institutions are undertaken.